Collision and rebound of ping pong balls on a rigid target. (15th December 2015) - Bao, R.H.; Yu, T.X.
Abstract: The collision and rebound behavior of ping pong balls impinging onto rigid target are studied. Three dimensionless dominant parameters are identified: (1) the ratio of the wall-thickness to the average radius of the ball; (2) the dimensionless initial velocity; and (3) the yield strain of the material. Depending on the dimensionless initial velocity, various collision and rebound behaviors of the ball are revealed: (1) When the initial velocity is low, the deformation of the ball remains purely elastic, for which the characteristic duration is theoretically obtained; (2) With the increase of initial velocity, the ball's cap begins to buckle and multiple impacts occur, leading to the increase of the restitution duration and the reduction of the coefficient of restitution (COR); (3) With the higher initial velocity, the ball's cap buckles permanently, leading to the disappearance of multiple impacts and a sudden drop of the restitution duration; consequently the COR decreases from 0.5 to 0.3; and (4) When the initial velocity is close to the material's yield velocity, the ball buckles into a non-axisymmetric mode. The simulation results are also compared with experimental ones. Furthermore, the effects of thickness-to-radius ratio, yield strain and coefficient of friction are also discussed. Graphical abstract: Highlights: Three dimensionless parameters are identified to govern the collision and rebound of ping pong balls on a rigid target. Closed-form expressions of collision duration and critical velocity are obtained. The dynamic deformation of the balls is found to be localized around the impact end. The dependence of coefficient of restitution (COR) on the collision velocity is revealed. The maximum rebounding velocity corresponds to about one quarter of the material's yield velocity.